A container ship traffic model for simulation studies - Wawrzyniak, Jakub; Drozdowski, Maciej; Sanlaville, Éric (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to develop a container ship traffic model for port simulation studies. Such a model is essential for terminal design analyses and testing the performance of optimization algorithms. This kind of studies requires accurate information about the ship stream to build test scenarios and benchmark instances. A statistical model of ship traffic is developed on the basis of container ship arrivals in eight world ports.
Keywords: benchmark instances; algorithm evaluation; data analysis; scheduling; container ship traffic modeling; marine logistics